Obesity due to melanocortin 4 receptor (MC4R) deficiency is associated with delayed gastric emptying. (25th October 2021) - Seelig, Eleonora; Henning, Elana; Keogh, Julia M.; Gillett, Daniel; Shin, Evelyn; Buscombe, John; van der Klaauw, Agatha A.; Farooqi, I. Sadaf
Abstract: Objective: People who are severely obese due to melanocortin‐4 receptor (MC4R) deficiency experience hyperphagia and impaired fullness after a meal (satiety). Meal‐induced satiety is influenced by hormones, such as peptide‐YY (PYY), which are released by enteroendocrine cells upon nutrient delivery to the small intestine. Design: We investigated whether gastric emptying and PYY levels are altered in MC4R deficiency. Methods: Gastric emptying was measured with a gastric scintigraphy protocol using technetium‐99m ( 99 Tc m )‐Tin Colloid for 3.5 h in individuals with loss of function MC4R variants and a control group of similar age and weight. In a separate study, we measured plasma PYY levels before and at multiple time points after three standardised meals given to individuals with MC4R deficiency and controls. Fasting PYY (basal secretion) and postprandial PYY levels were measured and the area under the curve and inter‐meal peak were calculated. Results: We found that gastric emptying time was significantly delayed and percentage meal retention increased in individuals with MC4R deficiency compared to obese controls. In addition, fasting and mean PYY secretion throughout the day were decreased in MC4R deficiency, whereas postprandial PYY secretion was unaltered. Conclusion: Delayed gastric emptying and reduced basal PYY secretion may contribute to impaired satiety in people with obesity due to MC4R deficiency.